The Effect of Entrepreneurial Competencies and Digital Technology Utilization on Business Performance: The Mediating Role of Financial Management - Duta Pryaguna J. Mustapa; Darman; Rahayu Agustina Ishak (Universitas Bina Mandiri Gorontalo, 2026)
This quantitative study evaluates the influence of business actors' competence and digitalization on the performance of MSMEs in Gorontalo Province, with financial management as a mediating variable. Using a sample of 51 MSMEs and PLS-SEM analysis (SmartPLS 4), this research fills the empirical gap due to the limited similar literature in that region. The results show that both competence and digitalization positively and significantly influence financial management and business performance. In addition to directly impacting performance, financial management is also proven to significantly mediate the relationship between these two aspects and performance achievement. Therefore, the sustainability of MSME businesses does not merely rely on general skills and digital aspects, but rather demands the implementation of healthy financial management.